Duce Kingdom - Folefac, Efualajong (Book collections on Project MUSE., 2013)
Duce Kingdom is a compelling mythical story of magic, sacrilege and violence, written in fine-styled first and third person dialogue and narration. The story commences with the rage of darkness into the official inauguration of the king, amid popular frustrations with the rigid laws and traditions of the kingdom. Sacrifice of virgins to gods, wars, romance and beheadings of criminals, make the future uncertain. The birth of Zalinda, a powerful sorcerer, redeems the kingdom from its woes.